Variations on a theme park : the new American city and the end of public space - Sorkin, Michael, 1948-2020 (New York : Hill and Wang, 1992)
America's cities are being rapidly transformed by a sinister and homogenous design. A new Kind of urbanism--manipulative, dispersed, and hostile to traditional public space--is emerging both at the heart and at the edge of town in megamalls, corporate enclaves, gentrified zones, and pseudo-historic marketplaces. If anything can be described as a paradigm for these places, it's the theme park, an apparently benign environment in which all is structured to achieve maximum control and in which the idea of authentic interaction among citizens has been thoroughly purged. In this bold collection, eight of our leading urbanists and architectural critics explore the emblematic sites of this new cityscape--from Silicon Valley to Epcot Center, South Street Seaport to downtown Los Angeles--and reveal their disturbing implications for American public life.
Variations on a theme park / Michael Sorkin -- The world in a shopping mall / Margaret Crawford -- Silicon Valley Mystery House / Langdon Winner -- New city, new frontier : the Lower East Side as wild, wild West / Neil Smith -- Inside exopolis : scenes from Orange County / Edward W. Soja -- Underground and overhead : building the analogous city / Trevor Boddy -- Fortress Los Angeles : the militarization of urban space / Mike Davis -- Cities for sale : merchandising history at South Street Seaport / M. Christine Boyer -- See you in Disneyland / Michael Sorkin.
Includes bibliographical references (pages 233-249).
Mode of access: Internet.
Keywords: Public spaces; City planning; City and town life; Cities and towns; Public spaces -- United States; City and town life -- United States; City planning -- United States; Cities and towns -- United States; United States